Aspectual Restriction on Sorting in Czech and Slovak - Mojmír Dočekal; Michaela Hulmanová; Aviv Schoenfeld (Languages)
This article is about the cross-linguistic universality of the so-called Universal Sorter, where a noun N means ‘kind of N’. We discuss two restrictions in two Slavic languages which are absent from English, pertaining to perfective verbs and numerically modified count nouns. We establish, first with introspective judgments (for Czech) and then experimentally (for Slovak), that both restrictions are present in a way which supports our analysis of the first restriction as stemming from Slavic, unlike English, having perfective verbs which force a completive reading of an incremental theme.